Transparency in the Tender Process of Regional Drinking Water Companies Amidst Unfair Competition - P. Soemartono, Gatot; Sriwijaya, Lenny (Journal of Law, Politic and Humanities, 2024)
The tender procurement system in Indonesia is frequently tarnished by unfair business competition practices such as tender monopolies. These actions hurt society and the government while also impeding the efficacy and efficiency of purchasing products and services. This study takes a qualitative approach, analyzing KPPU decisions and doing literature reviews. The research findings indicate various factors contributing to the complexity of unfair business competition within tender monopolies, including a lack of accountability and transparency, lax regulation and law enforcement, entrepreneurial collusion, and external political and economic influences. Additionally, this research proposes solutions for these problems, such as boosting accountability and transparency, fortifying legal frameworks and law enforcement, and encouraging public and business education about fair competition, and establishing an effective monitoring and evaluation system to prevent unfair practices